Performance of brazilian nurses in the school environment: Narrative review (Research, Society and Development, 2021)
Introduction: The school context represents a strategic space for the acquisition of knowledge, skills, changes in behavior and lifestyles, as it is a place where the student develops bonds and usually stays for a long time. Objective: To describe the evidence from studies on the role of Brazilian nurses in the school environment. Method: This is a narrative review of the literature. The searches were carried out between April and May 2020, in the following databases: Latin American and Caribbean Literature on Health Sciences (Lilacs), Scientific Electronic Library Online (Scielo), Database on Nursing Brazilian Bibliography (BDEnf) via the Virtual Health Library (VHL) and in gray literature. The Health Sciences Descriptors (DeCS) and the keywords related to the theme were used: School nursing, School health, Health promotion, School nursing, School health and Health promotion. The critical analysis of the studies and the synthesis of bibliographic data were carried out in a descriptive way, grouped by themes relevant to the studied subject. Results: The results found allowed the comments to be presented in three major thematic categories, namely: The school as an environment for nurses' intervention for comprehensive and healthy education; The significant contribution of nurses in the Brazilian school environment and the Influence of education and health promotion in the school environment. Final considerations: It was noticed that the role of nurses in the school environment is essential for the development and growth of students and also the health promotion of all actors involved in the school environment.